Chronic exposure to diesel engine exhaust and alteration of the airway bacteriome - Menghui Jiang; Yongwei Yan; Tao Wang; Bojia Wang; Yanting Li; Jinglong Tang; Yuxin Zheng (Ecotoxicology and Environmental Safety)
The detrimental effects of diesel engine exhaust (DEE) on public health are receiving increasing attention, particularly concerning respiratory health. Our understanding of the associations of the airway bacterial ecosystem with exposure to DEE and respiratory health remains limited. Our study aimed to identify the airway bacterial signature and assess its correlation with respiratory health in occupational populations. In this study, we collected induced sputum from 54 diesel-exposed workers and 52 unexposed controls. The exposed participants experienced lower forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) than controls. Importantly, the overall airway bacterial signature and assemblage in exposed individuals differed significantly from controls. The relative abundance of Prevotella nanceiensis, Prevotella shahii, Aggregatibacter segnis, and Lachnoanaerobaculum umeaense displayed remarkable differences between the two groups. Furthermore, exposed individuals showed a less robust correlation network and fewer keystone species in their airway bacteriome than controls. Furthermore, the Spearman analysis indicated notable correlations of specific species with carbon content in airway macrophages (CCAM), club cell protein (CC16), FVC and FEV1. Taken together, our study provided new information on the difference in the airway bacterial signature under exposure to DEE and supported a potential new link between specific species and lung function in occupational populations.